2017
DOI: 10.1021/acs.macromol.7b01438
|View full text |Cite
|
Sign up to set email alerts
|

Water-Triggered Ductile–Brittle Transition of Anisotropic Lamellar Hydrogels and Effect of Confinement on Polymer Dynamics

Abstract: We study the effect of dehydration on the structure and mechanical properties of anisotropic lamellar hydrogels, consisting of alternative stacking of several thousands of nanoscale rigid bilayers from amphiphilic poly­(dodecyl glyceryl itaconate) (PDGI) and submicroscale soft hydrogel layers from hydrophilic polyacrylamide (PAAm) networks. We found that the layered microstructure is well preserved with dehydration, and a ductile–brittle transition occurs at the critical water content. This transition is relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 34 publications
0
20
1
Order By: Relevance
“…However, when C SA exceeded 10 wt%, the relationship of E ∼ C v,p 3 was observed, no longer obeying the rubber elasticity theory. It should be noted that the transition of two power law regions in this research is quite different from the water‐triggered ductile‐brittle transition reported by Gong and co‐workers owing to two reasons. First, the critical C W value relative to the modulus transition in the current work was ≈80 wt%, corresponding to a molar composition of water/G (or M) unit ≈ 40/1, which showed that more water molecules were hydrated in per G or M unit.…”
contrasting
confidence: 92%
“…However, when C SA exceeded 10 wt%, the relationship of E ∼ C v,p 3 was observed, no longer obeying the rubber elasticity theory. It should be noted that the transition of two power law regions in this research is quite different from the water‐triggered ductile‐brittle transition reported by Gong and co‐workers owing to two reasons. First, the critical C W value relative to the modulus transition in the current work was ≈80 wt%, corresponding to a molar composition of water/G (or M) unit ≈ 40/1, which showed that more water molecules were hydrated in per G or M unit.…”
contrasting
confidence: 92%
“…From previously reported studies with polyacrylamide (PAAm) hydrogel system 26 , the exponent ν is~1 for dilute or semi-dilute state (ϕ p,v < 0.7) and~45 for concentrated state (ϕ p,v > 0.7). For the AINOs, ν is 12.1 at the brittle region, 14.7 at the soft region, and 60 at the transient region with two transition of power laws across the composition.…”
Section: Resultsmentioning
confidence: 99%
“…11 Lamellar hydrogels, 12 discovered in 1996 by Safinya and Davidson and composed of a phospholipid Lα phase stabilized by a polymer-grafted lipid, were the first example of an elastic 2D self-assembled material at small concentration (<10 wt%). Since then, lamellar hydrogels (LH) were obtained by polymer-stabilization, 13 or by combining a lamellar phase with a gelator. 14,15 The first polymer-free LH, based on surfactant mixtures or lipid/surfactants, are reported only in 2014.…”
Section: Introductionmentioning
confidence: 99%